2021
DOI: 10.3389/fcvm.2021.719058
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences, Estrogen Metabolism and Signaling in the Development of Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a complex and devastating disease with a poor long-term prognosis. While women are at increased risk for developing PAH, they exhibit superior right heart function and higher survival rates than men. Susceptibility to disease risk in PAH has been attributed, in part, to estrogen signaling. In contrast to potential pathological influences of estrogen in patients, studies of animal models reveal estrogen demonstrates protective effects in PAH. Consistent with this latter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 209 publications
(141 reference statements)
0
13
0
Order By: Relevance
“…In addition, Sweeney et al showed that 80% of the female PAH patients reported prior use of exogenous estrogen therapy, either in the form of oral contraceptive pills (premenopausal women) or as hormone replacement therapy (postmenopausal women) [52]. On the other hand, female PAH patients demonstrate superior right heart function and survival rates than their male counterparts [66]. Additionally, several studies using animal models have suggested that estrogens may have a protective role in the PAH setting; however, we must be cautious when extrapolating these findings to humans [66].…”
Section: Estrogen Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Sweeney et al showed that 80% of the female PAH patients reported prior use of exogenous estrogen therapy, either in the form of oral contraceptive pills (premenopausal women) or as hormone replacement therapy (postmenopausal women) [52]. On the other hand, female PAH patients demonstrate superior right heart function and survival rates than their male counterparts [66]. Additionally, several studies using animal models have suggested that estrogens may have a protective role in the PAH setting; however, we must be cautious when extrapolating these findings to humans [66].…”
Section: Estrogen Exposurementioning
confidence: 99%
“…On the other hand, female PAH patients demonstrate superior right heart function and survival rates than their male counterparts [66]. Additionally, several studies using animal models have suggested that estrogens may have a protective role in the PAH setting; however, we must be cautious when extrapolating these findings to humans [66]. This controversy has been often referred to as the "estrogen paradox".…”
Section: Estrogen Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…PAH is a sexually dimorphic disease with female predominance ( 6 ). Sex differences are attributed, in major part, to the role of sex hormones and, importantly, estrogen metabolites in PAH pathophysiology ( 6 , 7 ). From work in patients with PAH, estrogenic activity is associated with the penetrance of PAH ( 8 , 9 ).…”
mentioning
confidence: 99%
“…Cumulatively, discrepancies between patients and animal models of PAH are commonly referred to as the “estrogen paradox” ( 7 ). The estrogen paradox is explained partly by the complexity of 17β-estradiol (E2) metabolism and the potential tissue-specific roles of the diverse estrogen metabolites ( 6 ). For example, the most abundant circulating estrogen, E2, appears to exert protective effects in the right ventricle in a variety of rodent models of PH ( 7 ).…”
mentioning
confidence: 99%